Distributed flexibility to maintain security margin through decentralised TSO–DSO coordination. (March 2023) - Nikkhah, Saman; Rabiee, Abbas; Soroudi, Alireza; Allahham, Adib; Taylor, Philip C.; Giaouris, Damian
Abstract: The increasing role of distribution networks as an active entity in the whole power and energy system, development of a unified power flow method to provide an integrated analysis of transmission and distribution networks becomes essential. Traditional methods have not addressed the challenge of voltage security in the coordination, while disconnecting the whole distribution network is considered as a solution for preventing major issues. This paper proposes a decentralised scheme for the coordination of transmission and distribution networks while maintaining the voltage security of the whole integrated system. At the transmission level, the transmission network operator (TSO) solves a centralised optimisation problem to minimise the system load curtailment while maintaining the system security margin. The TSO communicates the required set-points in the interface with distribution grids to the distribution system operators (DSOs.) At the distribution level, the DSOs utilise their available distributed flexibilities, such as conservation voltage reduction and feeder reconfiguration, to provide the required set-points and preserve the whole system security margin, with minimum load curtailment. This decentralised optimisation scheme preserves the system security with minimum information exchange between operators, as well as minimum physical load curtailment. The distributed flexibilities of all DSOs are utilised to meet the required security margin of the whole system. The proposed TSO–DSO coordination model is applied to the IEEE 118-bus transmission network, and the 83-bus practical distribution network of Taiwan Power Company and IEEE 33-bus feeder are considered as the connected distribution networks. The results show that the distributed flexibilities are capable of reducing the system demand to preserve the desired security margin, without any need for imposing direct load curtailment. Highlights: A decentralised approach is proposed for TSO–DSO coordination. Loadability margin is introduced as the security criteria for TSO–DSO coordination. Conservation voltage reduction and network reconfiguration for providing flexibility. Coordination is provided with the minimum volume of data exchange. Distribution network of Taiwan Power Company is used as practical test system.